Coadministration of ivermectin and abamectin affects milk pharmacokinetics of the antiparasitic clorsulon in Assaf sheep - Blanco-Paniagua, Esther; Álvarez-Fernández, Laura; Millán-García, Alicia; Rivas, Guillermo; Álvarez, Ana I.; Merino, Gracia (Frontiers in Veterinary Science, 2023)
In veterinary field, drug exposure during milk production in dairy cattle is considered a major health problem which concerns dairy consumers. The induced expression of the ABC transporter G2 (ABCG2) in the mammary gland during lactation plays a significant role in the active secretion of many compounds into milk. The main objective of this study was to determine the involvement of ABCG2 in the secretion into milk of the antiparasitic clorsulon in sheep as well as the possible effect of the coadministration of model ABCG2 inhibitors such as macrocyclic lactones on this process. Cells transduced with the ovine variant of ABCG2 were used to carry out in vitro transepithelial transport assays in which we showed that clorsulon is a substrate of the ovine transporter. In addition, ivermectin and abamectin significantly inhibited clorsulon transport mediated by ovine ABCG2. In vivo interactions were studied in Assaf sheep after coadministration of clorsulon (in DMSO, 2 mg/kg, s.c.) with ivermectin (Ivomec ® , 0.2 mg/kg, s.c) or abamectin (in DMSO, 0.2 mg/kg, s.c.). After ivermectin and abamectin treatment, no relevant statistically significant differences in plasma levels of clorsulon were reported between the experimental groups since there were no differences in the area under the plasma concentration-curve (AUC) between clorsulon treatment alone and coadministration with macrocyclic lactones. With regard to milk, total amount of clorsulon, as percentage of dose excreted, did not show statistically significant differences when macrocyclic lactones were coadministered. However, the AUC for clorsulon significantly decreased (p < 0.05) after coadministration with ivermectin (15.15 ± 3.17 µgꞏh/mL) and abamectin (15.30 ± 3.25 µgꞏh/mL) compared to control group (20.73 ± 4.97 µgꞏh/mL). Moreover, milk parameters such as half-life (T1/2) and mean residence time (MRT) were significantly lower (p < 0.05) after coadministration of macrocyclic lactones. This research shows that the milk pharmacokinetics of clorsulon is affected by the coadministration of ABCG2 inhibitors, reducing drug persistence in milk.